THE EFFECT OF WORK-FAMILY CONFLICT, WORKLOAD AND SELF-EFFICACY ON WORK STRESS WITH SOCIAL SUPPORT AS A MODERATING VARIABLE - Af'idah, Lina; Kabib, Nur (Journal of Islamic enterpreneurship and Management, 2022)
The purpose of this study was to determine and analyze the effect of work-family conflict (X1), workload (X2), self-efficacy (X3), work stress (Y) and social support (Z) on nurses at Muhammadiyah Hospital Rodliyah Achid Moga Hospital. Data collection in this study was carried out by distributing questionnaires which were distributed to nurses at Muhammadiyah Rodliyah Achid Moga Hospital. The sample in this study amounted to 40 respondents and the technique used was the saturated sample technique. From the results of data analysis, it shows that: (1) Work-family conflict has a positive and significant effect on work stress. (2) Workload has a positive and significant effect on work stress. (3) Self-efficacy has a negative and significant effect on work stress. (4) Social support is able to moderate the effect of work-family conflict on work stress. (5) Social support is able to moderate the effect of workload on work stress. (6) Social support is not able to moderate the effect of self-efficacy on work stress on nurses at Muhammadiyah Rodliyah Achid Moga Hospital.Keywords: Work-Family Conflict, Workload, Self-Efficacy, Social Support and Work Stress.